Embedding Social Emotional Learning into School Routines: Daily Practices Based on Whole School Approach and Trikon Values to Strengthen 21st-Century Communication Skills - Rona Romadhianti; Muhammad Fuad; Nurlaksana Eko Rusminto; Muhammad Nurwahidin (Jurnal Ilmu Pendidikan, 2025)
This study aims to develop and embed Social Emotional Learning (SEL) into daily school routines as a strategy to foster 21st-century communication skills among senior high school students in Indonesia. Grounded in the Whole School Approach (WSA) and Trikon values from Ki Hadjar Dewantara’s philosophy, this research emphasizes the role of daily practices—such as morning greetings, emotional check-ins, reflective sharing, and optimistic closure as integral instruments to cultivate students’ communication competence. Unlike temporary or subject-based instructional strategies, embedding SEL into school routines offers a sustainable and systemic cultural transformation within the school environment. The study employed the Research and Development (R&D) method using the Four-D Model (Define, Design, Develop, Disseminate). Participants were Grade XI students from three senior high schools representing diverse geographical and socio-cultural contexts. Data were collected through observations, interviews, journals, and authentic communication assessments, analyzed using a qualitative-dominant mixed methods design to capture both behavioral narratives and measurable indicators. Findings reveal that integrating SEL into school routines enhances students’ ability to express themselves clearly, listen actively, collaborate empathetically, and engage in constructive dialogue. Teachers reported that the routines created a more supportive and inclusive learning atmosphere, while students demonstrated improved confidence and resilience in academic and social interactions. In conclusion, embedding SEL into daily routines not only strengthens communication skills but also institutionalizes character education through culturally rooted practices. This model provides a replicable framework for Indonesian schools to advance holistic education, aligning with the vision of the Kurikulum Merdeka and the Profile of Pancasila Students.